2009
DOI: 10.1038/jid.2008.354
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UVB-Induced Skin Tumor Development by Drinking Green Tea Polyphenols Is Mediated Through DNA Repair and Subsequent Inhibition of Inflammation

Abstract: Consumption of green tea polyphenols (GTPs) in drinking water prevents photocarcinogenesis in mice; however, the molecular mechanisms underlying this effect have not been fully elucidated. Using interleukin (IL)-12p40 knockout (IL-12-KO) mice and their wild-type counterparts and an established photocarcinogenesis protocol, we found that although administration of GTPs (0.2%, w/v) in drinking water significantly reduced UVB-induced tumor development in wild-type mice, this treatment had a non-significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 41 publications
5
106
0
Order By: Relevance
“…The CPDs expression was found in cytoplasm and nucleus cells of epidermal and dermal layer in UVB-exposed group (Figure 1). It was showed that UVB exposure penetrated into dermal layer skin mice, this result consistent with the previous study when UVB (180mJ/cm 2 ) exposed on the SKH-1 hairless, C3H/HeN and IL-12p40KO mice (Meeran et al, 2009;Afag et al, 2010). UV-B radiation can penetrate the skin to depth approximate 160-180 µm.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The CPDs expression was found in cytoplasm and nucleus cells of epidermal and dermal layer in UVB-exposed group (Figure 1). It was showed that UVB exposure penetrated into dermal layer skin mice, this result consistent with the previous study when UVB (180mJ/cm 2 ) exposed on the SKH-1 hairless, C3H/HeN and IL-12p40KO mice (Meeran et al, 2009;Afag et al, 2010). UV-B radiation can penetrate the skin to depth approximate 160-180 µm.…”
Section: Resultssupporting
confidence: 81%
“…Highest expression of CPDs showed at 2 hours after UVB exposure ( Figure 2). Balb/c mice showed less sensitive to UVB irradiation than hairless mice which had the highest CPDs expression at 0.5h after 180mJ/cm 2 UVB irradiation on female C3H/HeN and IL-12p40 KO mice (Meeran et al, 2009) and at 1h after a single dose of 3xMED (Minimal Erythema Dose) of Solar Simulator UV in hairless mice (Widyarini, 2006). These indicated that UVB-induced CPDs formation was influenced of wave length, intensity of radiation and animal sensitivity.…”
Section: Resultsmentioning
confidence: 80%
“…We decided to analyse these markers as they belong to three different marker groups that may be related to cancer and/or to inflammatory diseases. p27, Skp2, Cox2, CycD1 and Ki67 are considered as tumour and/or proliferation markers (Huang et al, 2003;Siggelkow et al, 2004;Adjei, 2005;Vig-Varga et al, 2006;Garg et al, 2008;Park et al, 2008;Chang et al, 2009;Meeran et al, 2009;Mukhopadhyay et al, 2009), ImAnOx and carbonyls are oxidative markers (Nyström, 2005;Bahar et al, 2007) and MMP-9, -3 and -2 are MMPs that are expressed in various pathological processes such as inflammation and cancer and also in response to infections (Korpos et al, 2009;Oikonomidi et al, 2009;Vanlaere and Libert, 2009). Enhanced oxidative stress characterises both inflammation and cancer; all other markers analysed were also shown previously to be associated with inflammation, as well as with oxidative stress, presumably mediated through the activation of NF-kB (Huang et al, 2003;Vig-Varga et al, 2006;Park et al, 2008;Gonda et al, 2009;Karalis et al, 2009;Ku et al, 2009;Perricone et al, 2009;Víctor et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To adapt to the continuous insult from excessive sun light exposure, plants developed physical, enzymatic and non-enzymatic mechanisms to not only protect but also to repair the damage done from indiscriminate exposure of UV radiation. Some of the secondary metabolites for example polyphenols such as green tea polyphenols have been studied [37]. Green tea polyphenols plays protective role by mediating DNA repair and reduction in skin inflammation.…”
Section: Photo Protective Mechanisms In Plantsmentioning
confidence: 99%